2022
DOI: 10.1039/d2fo01585d
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched soybean peptides pretreatment attenuates lung injury in mice induced by fine particulate matters (PM2.5) through inhibition of TLR4/NF-κB/IκBα signaling pathway and inflammasome generation

Abstract: This study aimed to identify and prepare peptides from selenium (Se)-enriched soybeans and determine whether dietary Se-enriched soybean peptides (Se-SPep) could inhibit lung injury in mice induced by fine particulate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Our previous study showed that selenium-enriched soybean peptides could alleviate PM2.5-induced lung damage in mice by inhibiting NLRP3, caspase-1 and ASC/TMS1 protein expressions and reducing the inflammatory factor concentration. 7 In this study, as shown in Fig. 6, Sep-1 and Sep-2 isolated and identified from SePPs significantly inhibited the expression of these proteins ( p < 0.05), reducing the release of downstream inflammatory factors IL-1β and IL-18.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Our previous study showed that selenium-enriched soybean peptides could alleviate PM2.5-induced lung damage in mice by inhibiting NLRP3, caspase-1 and ASC/TMS1 protein expressions and reducing the inflammatory factor concentration. 7 In this study, as shown in Fig. 6, Sep-1 and Sep-2 isolated and identified from SePPs significantly inhibited the expression of these proteins ( p < 0.05), reducing the release of downstream inflammatory factors IL-1β and IL-18.…”
Section: Resultssupporting
confidence: 60%
“…Zhang et al found that selenium-enriched soybean peptides could reduce lung inflammation by influencing TLR4/NF-κB/IκBα and NLRP3/ASC/caspase-1 signaling pathways in a PM2.5-induced lung injury model in mice. 7 Liu et al reported that selenium-enriched soybean peptides could alleviate CCl 4 -induced liver fibrosis by enhancing GSH-Px activity and GSH content, and improving antioxidant capacity. 8 However, most of the selenium-enriched peptides used in reported studies tend to be mixtures of multiple selenium-enriched and common peptides, which makes it difficult to identify which of these components play key roles.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum recommended dose of SP for human is 10 g/day (http://www.nhc.gov.cn/sps/s7892/202205/7777634cb5994c308e12cf3a3255c622.shtml). Due to the method of Zhang, the corresponding gavage dose for mice was calculated to be 1.52 mg/g BW/day (Zhang et al., 2022). Thus, the mice of SP‐L, SP‐M, and SP‐H groups were administrated with 0.76, 1.52, and 3.03 mg SP/g BW/day, respectively.…”
Section: Methodsmentioning
confidence: 99%